2017
DOI: 10.1016/j.cortex.2016.12.022
|View full text |Cite
|
Sign up to set email alerts
|

The right angular gyrus controls spontaneous eyeblink rate: A combined structural MRI and TMS study

Abstract: Spontaneous eyeblink rates vary greatly between people, from several to a few dozen blinks per minute. Nevertheless, it remains unknown which brain region controls generation of spontaneous eyeblinks. To investigate this issue, the present study examined brain anatomy, which reflects inter-individual variability in eyeblink rate using structural magnetic resonance images with voxel-based morphometry (VBM) in 57 participants. The gray matter volume of the right angular gyrus (rAG) was positively associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…We speculated that the functional damage of proprioception might be caused by the decrease of the functional connectivity of the supramarginal gyrus caused by basal ganglia damage. The angular gyrus is related to integrating semantic information and is the neurobiological basis of conceptual combination (34). A voxel-based morphometry (VBM) analysis of stroke showed that the reduction of angular gray matter volume might result in the decrease of semantic processing ability and speech orientation sensitivity (35).…”
Section: Discussionmentioning
confidence: 99%
“…We speculated that the functional damage of proprioception might be caused by the decrease of the functional connectivity of the supramarginal gyrus caused by basal ganglia damage. The angular gyrus is related to integrating semantic information and is the neurobiological basis of conceptual combination (34). A voxel-based morphometry (VBM) analysis of stroke showed that the reduction of angular gray matter volume might result in the decrease of semantic processing ability and speech orientation sensitivity (35).…”
Section: Discussionmentioning
confidence: 99%
“…EBR was defined as the ratio between the total number of blinks in a phase and the duration of the phase in minutes. To control for the large inter-individual variability, we normalized the data by computing the ratio between the EBR collected during the tasks and the rest phases, and the respective EBR collected during the baseline for each participant [2,29].…”
Section: Eeg Recording and Preprocessingmentioning
confidence: 99%
“…Eye blinks can be produced as a reflex in response to threatening stimulation of the corneal surface, as a voluntary act or spontaneously in absence of any stimulation and volition [1]. In human adults, spontaneous eye blinks appear every 3-5 seconds, with an average eye blink rate (EBR) of ∼20 blinks per minute [2,3], although with a large inter-individual variability [1,4].…”
Section: Introductionmentioning
confidence: 99%
“… ( a ) From References [ 5 , 8 , 14 , 15 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]; ( b ) (▲) from Reference [ 52 ] and (●) Reference [ 53 ]; ( c , d , f ) hydrocarbon chain order at 33.4 ° C and phase transition parameters for the lipid order (gel) to disorder (liquid crystal) phase transition of human meibum. (●) Reference [ 26 ]; (■) Reference [ 1 ]; (▲) this study and (▼) Reference [ 25 ].…”
Section: Figurementioning
confidence: 99%